Accelerating Recurrent Neural Network Training via Two Stage Classes and Parallelization - Zweig, Geoffrey; Levit, Michael; Chang, Shawn (ASRU, 2013)
Recurrent neural network (RNN) language models have proven to be successful to lower the perplexity and word error rate in automatic speech recognition (ASR). However, one challenge to adopt RNN language models is due to their heavy computational cost in training. In this paper, we propose two techniques to accelerate RNN training: 1) two stage class RNN and 2) parallel RNN training. In experiments on Microsoft internal short message dictation (SMD) data set, two stage class RNNs and parallel RNNs not only result in equal or lower WERs compared to original RNNs but also accelerate training by 2 and 10 times respectively. It is worth noting that two stage class RNN speedup can also be applied to test stage, which is essential to reduce the latency in real time ASR applications.